2008
DOI: 10.1007/s00345-008-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncological risk of laparoscopic surgery in urothelial carcinomas

Abstract: Oncological results of the laparoscopic approach are difficult to compare with those of open surgery. However, recent series have not reported unusual tumour dissemination or a higher rate of recurrence with this approach. Laparoscopic techniques are not yet standard of care in invasive urothelial carcinomas. Long-term assessment is ongoing and awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 62 publications
1
22
0
3
Order By: Relevance
“…Indeed, in urothelial cancers, laparoscopy and the pneumoperitoneum may be a potential source of tumor cell spread [31]. This must be avoided by respecting the oncologic principles of open surgery, including not opening the urinary tract, gentle manipulation of tissue, and the use of an endobag.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in urothelial cancers, laparoscopy and the pneumoperitoneum may be a potential source of tumor cell spread [31]. This must be avoided by respecting the oncologic principles of open surgery, including not opening the urinary tract, gentle manipulation of tissue, and the use of an endobag.…”
Section: Discussionmentioning
confidence: 99%
“…It has been feared that tumor dissection during laparoscopic procedures may be associated with a higher risk of recurrence. 2 Although this remains a matter of controversy, 3 one randomized controlled trial, comparing laparoscopic nephroureterectomy (LNU) with open nephroureterectomy (ONU), showed that oncologic outcomes were comparable for both groups. 4 However, there has been no study of oncologic outcomes after LNU compared with hand-assisted laparoscopic nephroureterectomy (HALNU) and ONU for patients with UUTUC.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Specific worries about the pneumoperitoneum, tumor manipulation, and specimen extraction are addressed. Some experimental studies reported that laparoscopic surgery could promote tumor growth and metastases.…”
Section: Discussionmentioning
confidence: 99%